Social behaviors of mentally-retarded students in physical education learning - Pamuji Sukoco (LPPM UNY, 2009)
This study is aimed at knowing the social behaviors of mentally-retarded students in education learning. As a survey study, the research involves the use of interview and observation as data collection procedures. The subjects of the study are 34 mentally-retarded students. The data is analyzed in a qualitative descriptive manner. The finding shows that mentally-retarded students need intensive and continuous consultation and support for their social behaviors in the physical education learning. In order for these students to participate well in the learning-teaching interaction, it is important to show to them the practical importance and value of doing physical practice. The instructions for the physical practice tasks should be brief and clear, and there should be not more than one instruction at a time. The teacher needs to understand students characteristics and choose the appropriate learning approach.